A novel method for quantitative geosteering using azimuthal gamma-ray logging. (February 2015) - Yuan, Chao; Zhou, Cancan; Zhang, Feng; Hu, Song; Li, Chaoliu
Abstract: A novel method for quantitative geosteering by using azimuthal gamma-ray logging is proposed. Real-time up and bottom gamma-ray logs when a logging tool travels through a boundary surface with different relative dip angles are simulated with the Monte Carlo method. Study results show that response points of up and bottom gamma-ray logs when the logging tool moves towards a highly radioactive formation can be used to predict the relative dip angle, and then the distance from the drilling bit to the boundary surface is calculated. Highlights: A new method is proposed for geosteering by using azimuthal gamma-ray logging. The new method can quantitatively determine the distance from the drilling bit to the boundary surface while the traditional geosteering method can only qualitatively guide the drilling bit in reservoirs. The response points of real-time upper and lower gamma line when the logging tool meets high radioactive formation are used to predict the relative dip angles, and then the distance from the drilling bit to the boundary surface is calculated.